2016
DOI: 10.1007/s00223-016-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroxine (T4), 3,5,3′-triiodo-l-thyronine (T3) and their Metabolites on Osteoblast Differentiation

Abstract: Studies involving human genetic mutations and mutant mouse models have provided irrevocable evidence for a key role for thyroid hormones (THs) in the regulation of skeletal growth. While T3 binds to TH receptors with higher affinity than T4, T4 occupied TH receptors have also been reported in the nucleus under euthyroid conditions raising the possibility that T4 bound nuclear receptors may be biologically relevant in thyroid syndromes with elevated free T4 and reduced T3 levels. We, therefore, evaluated the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…There are also data showing that in vitro thyroid hormones affect the energy metabolism in the bone remodelling process. T4 has been found to induce bone formation, differentiation, and mineralization in osteoblast- or osteoblast-like cells [27, 28]; more importantly, Gouveia et al revealed that T3 acted on the osteoblast-like cell mitochondrial gene ATPase 6 [29]. Although Kanatani et al discovered that T3 directly stimulated osteoclast differentiation [6] and Ma and Dai suggested that T3 stimulated osteoclast differentiation indirectly [30], only a few studies have investigated the effect of T4 on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also data showing that in vitro thyroid hormones affect the energy metabolism in the bone remodelling process. T4 has been found to induce bone formation, differentiation, and mineralization in osteoblast- or osteoblast-like cells [27, 28]; more importantly, Gouveia et al revealed that T3 acted on the osteoblast-like cell mitochondrial gene ATPase 6 [29]. Although Kanatani et al discovered that T3 directly stimulated osteoclast differentiation [6] and Ma and Dai suggested that T3 stimulated osteoclast differentiation indirectly [30], only a few studies have investigated the effect of T4 on osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical case–control study has shown that hyperthyroidism can cause net bone loss, decreased bone mineral density (BMD), and osteoporosis and increase the risk for fractures [1]. Both animal and clinical studies have shown that subjects with hyperthyroidism had higher bone resorption rates and bone formation marker levels [2-4] and that excessive levels of thyroid hormones might stimulate both osteoblast and osteoclast differentiation, however, the latter was more predominantly observed [5, 6]. Hyperthyroidism led to a higher frequency of bone remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the thyroid hormone (TH) played a vital role in energy metabolism since high load of TH enhance the metabolism of body substances. It was found that T4 had a positive effect on bone formation, differentiation, and mineralization in osteoblasts [19,20] . Also, excessive T4 levels might promote both osteoclast and osteoblast bioenergetics by strengthening the oxidative phosphorylation-TCA cycle-glycolysis pathway [14] .…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 mRNA levels were increased in MC3T3-E1 cells after treatment with THs, and the increased levels were positively correlated with TH concentrations. Furthermore, their metabolites, including T2 and rT3, could also promote the increase in IGF-1 mRNA levels ( 46 ) ( Figure 3 ).…”
Section: Effects Of Ths On Bonementioning
confidence: 99%